EVALUASI PERTAMBAHAN BOBOT BADAN, KONSUMSI DAN KONVERSI RANSUM AYAM KAMPUNG SUPER YANG DIBERI TEPUNG KUNYIT - Sabrin Mohamad; Fahria Datau; Nibras Karnain Laya (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
The purpose of this study was to evaluate body weight gain (PBB), ration consumption and ration conversion of Kampung Super chickens fed with turmeric flour in their rations. Single factor analysis was used in this study. Turmeric flour was given in stages: 0% (control), 2%, 4%, and 6%. Based on the results of the evaluation for ration consumption, it showed that the provision of turmeric flour was not significantly different (P 0.05) on the ration of super native chicken consumption. The average feed consumption is 324.39-338.69 g / head. Evaluation of body weight gain, showed that giving turmeric flour had a significant effect (P 0.05) on body weight gain. The ration conversion evaluation showed that the use of turmeric flour had a significant effect (P 0.05) on the ration conversion of Kampung Super chickens. The addition of 2-6% turmeric flour to native chicken rations showed an increase in body weight, a decrease in ration conversion. The recommendation for using turmeric in the super native chicken ration is 4% of the total basal ration